Percutaneous closure of left atrial appendage significantly affects lipidome metabolism - Yücel, Gökhan; Behnes, Michael; Barth, Christian; Wenke, Annika; Sartorius, Benjamin; Yazdani, Babak; Rusnak, Jonas; Saleh, Ahmad; Hoffmann, Ursula; Fastner, Christian; Lang, Siegfried; Zhou, Xiao-Bo; et al. (Scientific reports, 2018)
Patients with non-valvular atrial fibrillation (AF) and a high risk for oral anticoagulation can be treated by percutaneous implantation of left atrial appendage occlusion devices (LAAC) to reduce the risk of cardio-embolic stroke. This study evaluates whether LAAC may influence lipid metabolism, which has never been investigated before. Patients with successful LAAC were included consecutively. Venous peripheral blood samples of patients were collected immediately before (T0, baseline) and 6 months after (T1, mid-term) LAAC. A targeted metabolomics approach based on electrospray ionization liquid chromatography-mass spectrometry (ESI-LC-MS/MS) and MS/MS measurements was performed. A total of 34 lipids revealed a significant change from baseline to mid-term follow-up after successful LAAC. Subgroup analysis revealed confounding influence by gender, age, diabetes mellitus type II, body mass index, left ventricular ejection fraction, creatinine and NT-proBNP. After multivariable adjustment within logistic regression models, these 34 lipids were still significantly altered after LAAC. Successful percutaneous LAAC may affect lipid metabolism and thereby may potentially affect pro-atherogenic and cardio-toxic effects.